Visual search behaviour in soccer: Which predictor could explain competitive level? - Bagatin, R. T.; Padilha, M. B.; Ribeiro, J.; Aquino, R.; Rago, V.; Oliveira, J.; Garganta, J.; Casanova, F. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: As one of the perceptual-cognitive skill, the visual search behaviour allows soccer players to seek relevant information that helps them in deciding the accurate actions to execute during a match. In this sense, the aim of this study was to identify which predictors of visual search behaviour during a prolonged intermittent exercise protocol could explain competitive level. Methods: Sixteen soccer players were separated in two groups of eight players each, according to Elite (mean age = 24.6 yr, SD=3.9 yr; Semi and professional level 5.1 yr, SD =2.4 yr) and Non-elite (mean age = 26.3 yr, SD=2.9 yr; amateur level = 2.1 yr, SD=2.4 yr). The Applied Science Laboratories (ASL) 3000 eye-movement registration system was used by participants during the whole protocol test. To simulate the physiological demands of a soccer game, an intermittent exercise protocol was used (Drust, Reilly, & Cable, 2000). The protocol was consisted in 119 minutes divided in first half (52 minutes), recovery phase (15 minutes) and second half (52 minutes). Data were collected in four moments of test sessions (1º and 2º in first half time, 3º and 4º in second half). The measures from visual search behaviour comprised the Number of fixation per locations (NFL) (ball, teammate, opposition, player in possession of the ball, and undefined), and mean fixation duration per trial. The undefined category was excluded (less than 1%). The inter-observer agreement value was 99% (were reanalysed 25% of the data). In order to explain the variance of the dependent variable logistical regression were performed, as well as the correlation coefficient of determination and Beta value ( ). The alpha significant value was set at .05. Results: The logistic regression model was statistically significant, x2 (1)=7.31 (p=0.007). The model effect size was 0.36 and correctly classified 50.0% of cases. The increasing tendency of fixation durations values on the player in possession of the ball could explain the expertise level (i.e. elite or not-elite) of soccer players (OR=0.99; p=0.04). Discussion: The results showed that the fixation durations on the player in possession of the ball could explain the competitive level when verified this variable in the 2º half time (3º moment). Thus, elite players demonstrated superior fixation duration on the player in possession of the ball. In this way, our results suggested that the superior performance of elite players was associated with the selectivity of the perceptual resources, also suggested by others researchers (Martins et al., 2014).